Double-layer composite misfire anti-static rubber pad and preparation method thereof

By adopting a double-layer composite structure of modified neoprene and chloroprene rubber, combined with vulcanization and pressurized composite technology, the problems of insufficient antistatic stability and ignition performance of existing antistatic floor mats in harsh environments are solved, and higher wear resistance and surface smoothness are achieved.

CN119898090AActive Publication Date: 2025-04-29CHUANGXUANBAO PANTUO ANTI STATIC TECH SHANGHAI CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510377113.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-29
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The existing anti-static floor mats have insufficient anti-static stability and ignition-free performance under frequent friction conditions and harsh environments, and have poor wear resistance and surface smoothness.

Method used

Modified chloroprene copolymerized by 2-chloro-1,3-butadiene and vinylpyridine are used as the main component of the surface layer, and combined with chloroprene rubber as the bottom layer, a double-layer composite fire-free anti-static rubber pad is prepared by vulcanization and pressurized composite technology.

Benefits of technology

The rubber pad is stable antistatic and significantly non-ignition performance under frequent friction conditions and harsh environments, while improving the wear resistance and surface smoothness of the surface layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898090A_ABST
    Figure CN119898090A_ABST
Patent Text Reader

Abstract

The invention discloses a double-layer composite misfire anti-static rubber pad and a preparation method thereof, and relates to the technical field of rubber pads. The prepared double-layer composite misfire anti-static rubber pad comprises a surface layer and a bottom layer attached to one side of the surface layer. Wherein the surface layer comprises modified chloroprene rubber; and the bottom layer comprises chloropropylene rubber. The preparation method comprises the following steps: firstly, respectively preparing a surface layer material and a bottom layer material, then respectively mixing and processing the prepared materials, and finally compounding, calendering and vulcanizing to obtain the double-layer compounded misfire anti-static rubber pad. The prepared double-layer composite misfire anti-static rubber pad is excellent in anti-static performance, the surface layer is smooth and wear-resistant, and the rubber pad has anti-static stability and remarkable misfire performance under the working condition of frequent friction and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of rubber pads, and in particular to a double-layer composite non-flammable antistatic rubber pad and a preparation method thereof. Background Art

[0002] In many industrial fields and special places with strict requirements for electrostatic protection, such as electronic chip manufacturing workshops and chemical production workshops, safety issues are always the top priority. On the one hand, these places often contain flammable and explosive substances, and tiny electrostatic sparks generated by friction electrification may cause catastrophic explosions, endangering the lives of people and huge amounts of property safety; on the other hand, static electricity accumulation can also damage precision electronic equipment, affecting their normal operation and service life, leading to product quality defects and huge economic losses. Therefore, it is necessary to develop a series of non-flammable anti-static rubber pads to ensure effective safety protection.

[0003] The design concept of the double-layer composite structure of non-flammable anti-static rubber mat was born. Through the combination of different functional layers, it is expected to integrate a variety of excellent properties, so that the rubber mat can ensure static protection and fire safety even under severe impact and friction.

[0004] The Chinese patent application with publication number CN 106079755A discloses an antistatic floor mat for a computer room, comprising a bottom layer and a surface layer. The bottom layer is a conductive rubber layer, the surface layer is a resin layer with antistatic properties, and the bottom layer and the surface layer are bonded by thermal bonding to form an antistatic floor mat. The combination of the surface layer and the bottom layer enables the floor mat to have good antistatic properties, and is not prone to warping, making it easy to install.

[0005] However, the antistatic floor mat produced by this solution has poor wear resistance and an uneven surface, which easily accumulates charges in the environment and generates friction static electricity. Therefore, it does not have the antistatic stability and significant non-ignition performance under frequent friction conditions and other harsh environments, and there is much room for improvement. Summary of the invention

[0006] In view of the deficiencies of the prior art, the present application provides a double-layer composite non-inflammable antistatic rubber pad and a preparation method thereof, using modified chloroprene rubber copolymerized with 2-chloro-1,3-butadiene and vinylpyridine as the main component of the surface layer, and using chloropropylene rubber as the main component of the bottom layer, preparing the surface layer rubber mix and the bottom layer rubber mix respectively, and then vulcanizing and pressurizing and compounding, and finally obtaining a double-layer composite non-inflammable antistatic rubber pad. The double-layer composite non-inflammable antistatic rubber pad has excellent antistatic performance, and the surface layer is smooth and wear-resistant, has antistatic stability under frequent friction conditions and significant non-inflammable performance, and has excellent performance and application value in dust-free antistatic application scenarios.

[0007] In order to achieve the above objectives, this application adopts the following technical solutions: In the first aspect, the present application provides a double-layer composite non-flammable antistatic rubber pad, comprising a bottom layer and a surface layer attached to one side of the bottom layer; the surface layer comprises modified chloroprene rubber; the bottom layer comprises chloropropylene rubber; the modified chloroprene rubber is copolymerized by 2-chloro-1,3-butadiene and vinyl pyridine; the structure of the modified chloroprene rubber is: , Wherein, n is an integer in the range of 10 to 20; m is an integer in the range of 50 to 100; and the surface roughness Ra value of the surface layer is 0.8 to 1.6 μm.

[0008] In a second aspect, the present application provides a method for preparing a double-layer composite non-flammable antistatic rubber pad, comprising the following steps: In a nitrogen-protected reactor, 2-chloro-1,3-butadiene and vinyl pyridine are copolymerized by an emulsion copolymerization method under the action of an emulsifier and an initiator, the reaction is stirred at a first set temperature for a first set time, and the material is washed and dried to obtain a modified chloroprene rubber; Putting the modified chloroprene rubber and the nitrile rubber into an internal mixer, and mixing them at a second set temperature for a second set time; Adding antioxidant and nano zinc oxide into an internal mixer, and continuing to internally mix at a second set temperature for a third set time; Adding aluminum hydroxide, white carbon black, antistatic agent, tricresyl phosphate and accelerator DM into the internal mixer in sequence, and mixing at the third set temperature for the fourth set time to prepare a surface layer rubber mixture; After the surface layer mixed rubber is allowed to stand for a fifth set time, it is put into an open mixer and pressed into sheets at a fourth set temperature and a first set pressure to obtain a calendered surface layer; Adding chloropropylene rubber and styrene-butadiene rubber into an internal mixer, and mixing at a fifth set temperature for a fourth set time; Adding superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into an internal mixer, and mixing at a sixth set temperature for a sixth set time; Add dioctyl sebacate, paraffin oil and accelerator CZ into the internal mixer in sequence, and continue to mix at the sixth set temperature for the sixth set time to obtain a base rubber mixture; After the bottom layer mixed rubber is allowed to stand for the seventh set time, it is put into an open mixer and pressed into sheets at the fourth set temperature and the first set pressure to obtain a calendered bottom layer; The calendered surface layer is covered on the calendered bottom layer, then put into a mold, sent into a drum vulcanizer, and vulcanized for an eighth set time at the seventh set temperature, the second set pressure and the first vulcanization speed, to finally produce a double-layer composite non-flammable antistatic rubber mat.

[0009] Beneficial technical effects: In the present application, the surface matrix material of the double-layer composite non-flammable antistatic rubber pad is modified chloroprene rubber, which is copolymerized by 2-chloro-1,3-butadiene and vinyl pyridine. On the one hand, the strong polarity of the vinyl pyridine unit changes the surface properties of the rubber molecules, making the modified chloroprene rubber have better surface activity and reducing the interfacial tension between the filler and the rubber, so that the filler is dispersed in the surface modified chloroprene rubber matrix, enhancing the mechanical properties and stability of the modified chloroprene rubber, making it more wear-resistant. On the other hand, the surface of the rubber pad is very smooth (surface roughness Ra value is 0.8~1.6μm), and even if the attached charge is easy to disperse evenly, it is not easy to cause static electricity accumulation due to surface roughness, and it is difficult to generate static electricity sparks. Finally, the rigid pyridine ring structure with strong polarity will form a dipole interaction with the chlorine atoms in the molecular chain, increase the cohesion between the polymer chains, and improve the flame retardant properties of the modified chloroprene rubber. The combination of multiple aspects makes the surface layer have good non-inflammability. Further, under the joint action of other fillers and additives in the surface layer, the rubber pad obtained still has stable antistatic properties under frequent friction conditions and other harsh environments. In addition, the bottom matrix material of the double-layer composite non-inflammable antistatic rubber pad is chloropropylene rubber, which has excellent chemical stability. After being combined with fillers and additives such as superconducting carbon black and metal powder, it can quickly conduct the generated static electricity to the ground to avoid static electricity accumulation and sparks. After the two layers are compounded by vulcanization and pressure, the combination is firm, which further enhances the antistatic and non-inflammable properties of the obtained double-layer composite non-inflammable antistatic rubber pad. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a structural diagram of a double-layer composite non-flammable antistatic rubber mat.

[0011] Figure 2 It is a schematic diagram of the process of preparing a double-layer composite non-flammable antistatic rubber mat.

[0012] Figure 3 This is a physical picture of the prepared double-layer composite non-flammable antistatic rubber mat.

[0013] Figure numerals: 1, bottom layer; 2, surface layer. DETAILED DESCRIPTION

[0014] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application clearer, the present application is further described in detail below in conjunction with the embodiments. However, this should not be understood as the scope of the present application being limited to the following examples. Without departing from the above-mentioned method ideas of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0015] In this application, the terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit the application.

[0016] As used in this application, the singular forms "for", "or", "an", "any" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0017] In addition, if the terms “first” or “second” appear, they are used for descriptive purposes only and should not be understood as indicating or implying relative importance.

[0018] In the first aspect, it comprises a bottom layer 1 and a surface layer 2 attached to one side of the bottom layer 1, such as Figure 1 As shown, the surface layer 2 includes modified chloroprene rubber; the bottom layer 1 includes chloropropylene rubber; the modified chloroprene rubber is copolymerized by 2-chloro-1,3-butadiene and vinyl pyridine; the structure of the modified chloroprene rubber is: , Wherein, n is an integer in the range of 10 to 20; m is an integer in the range of 50 to 100; and the surface roughness Ra value of the surface layer 2 is 0.8 to 1.6 μm.

[0019] In a feasible implementation, the surface layer 2 further includes nitrile rubber, aluminum hydroxide, white carbon black, an antistatic agent, tricresyl phosphate, an antioxidant, nano zinc oxide and a promoter DM.

[0020] In a feasible implementation, the antistatic agent includes at least one of fatty alcohol polyoxyethylene ether, hexadecyltrimethylammonium bromide and octadecyldimethylbenzylammonium chloride.

[0021] In a possible implementation, the antioxidant includes at least one of the antioxidant 2246 and the antioxidant 264 .

[0022] In a feasible implementation scenario, in the surface layer 2, the mass ratio of modified chloroprene rubber, nitrile rubber, aluminum hydroxide, white carbon black, antistatic agent, tricresyl phosphate, antioxidant, nano zinc oxide and accelerator DM is (30~50): (15~20): (10-15): (10~20): (5~10): (3~10): (1~3): (2~5): (1~2).

[0023] In a feasible implementation, the bottom layer 1 further comprises styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ.

[0024] In a feasible implementation scenario, in the bottom layer 1, the mass ratios of chloropropylene rubber, styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ are (40-50): (10-15): (15-25): (5-10): (10-20): (1-3): (5-10): (3-10): (1-2).

[0025] In a second aspect, the present application provides a method for preparing a double-layer composite non-flammable antistatic rubber pad, such as Figure 2 As shown, the following steps are included: In a nitrogen-protected reactor, 2-chloro-1,3-butadiene and vinyl pyridine are copolymerized by an emulsion copolymerization method under the action of an emulsifier and an initiator, the reaction is stirred at a first set temperature for a first set time, and the material is washed and dried to obtain a modified chloroprene rubber; Putting the modified chloroprene rubber and the nitrile rubber into an internal mixer, and mixing them at a second set temperature for a second set time; Adding antioxidant and nano zinc oxide into an internal mixer, and continuing to internally mix at a second set temperature for a third set time; Adding aluminum hydroxide, white carbon black, antistatic agent, tricresyl phosphate and accelerator DM into the internal mixer in sequence, and mixing at the third set temperature for the fourth set time to prepare a surface layer rubber mixture; After the surface layer mixed rubber is allowed to stand for a fifth set time, it is put into an open mixer and pressed into sheets at a fourth set temperature and a first set pressure to obtain a calendered surface layer 2; Adding chloropropylene rubber and styrene-butadiene rubber into an internal mixer, and mixing at a fifth set temperature for a fourth set time; Adding superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into an internal mixer, and mixing at a sixth set temperature for a sixth set time; Add dioctyl sebacate, paraffin oil and accelerator CZ into the internal mixer in sequence, and continue to mix at the sixth set temperature for the sixth set time to obtain a base rubber mixture; After the bottom layer mixed rubber is allowed to stand for the seventh set time, it is put into an open mixer and pressed into a sheet at the fourth set temperature and the first set pressure to obtain a calendered bottom layer 1; The calendered surface layer 2 is covered on the calendered bottom layer 1, and then put into a mold, sent into a drum vulcanizer, and vulcanized for an eighth set time at the seventh set temperature, the second set pressure and the first vulcanization speed, and finally a double-layer composite non-flammable antistatic rubber mat is made, such as Figure 3 shown.

[0026] In a feasible implementation, the emulsifier includes any one of sodium dodecylbenzene sulfonate, sodium stearate and sodium dodecyl sulfate; the initiator includes any one of potassium persulfate and ammonium persulfate; the mass ratio of 2-chloro-1,3-butadiene, vinyl pyridine, emulsifier and initiator is (70~85):(10~30):(2~5):(0.2~0.8).

[0027] In a feasible implementation scenario, the first set temperature is 40~50℃; the second set temperature is 55~65℃; the third set temperature is 70~80℃; the fourth set temperature is 150~160℃; the fifth set temperature is 65~75℃; the sixth set temperature is 75~85℃; and the seventh set temperature is 160~170℃.

[0028] In a feasible implementation scenario, the first set time is 8~12h; the second set time is 8~12min; the third set time is 5~10min; the fourth set time is 10~15min; the fifth set time is 12~24h; the sixth set time is 15~20min; the seventh set time is 6~12h; and the eighth set time is 20~25min.

[0029] In a feasible implementation scenario, the first set pressure is 10-15 MPa; the second set pressure is 15-18 MPa; and the first vulcanization speed is 0.1-0.3 m / min.

[0030] In a feasible implementation, the thickness of the surface layer 2 is controlled to be 0.4-0.5 μm; the thickness of the bottom layer 1 is controlled to be 1.5-4.6 μm; The following will specifically describe a double-layer composite non-flammable antistatic rubber pad and a preparation method thereof provided by the present application in combination with different embodiments.

[0031] Embodiment 1:

[0032] like Figure 2 As shown, a method for preparing a double-layer composite non-flammable antistatic rubber pad comprises the following steps: 1. In a nitrogen-protected reactor, 2-chloro-1,3-butadiene and vinyl pyridine were copolymerized by emulsion copolymerization under the action of sodium dodecylbenzene sulfonate and potassium persulfate, and the reaction was stirred at 45°C for 10 hours. The material was washed and dried to obtain modified chloroprene rubber; The mass ratio of 2-chloro-1,3-butadiene, vinylpyridine, sodium dodecylbenzenesulfonate and potassium persulfate is 75:20:4.5:0.5; 2. Add the modified chloroprene rubber and nitrile rubber into an internal mixer and mix them at 55°C for 8 minutes; 3. Add antioxidant 2246 and nano zinc oxide into the internal mixer and continue mixing at 55°C for 5 minutes; 4. Add aluminum hydroxide, white carbon black, fatty alcohol polyoxyethylene ether, tricresyl phosphate and accelerator DM into the internal mixer in sequence, and mix at 70°C for 10 minutes to prepare the surface layer rubber mixture; The mass ratio of modified chloroprene rubber, nitrile rubber, aluminum hydroxide, white carbon black, fatty alcohol polyoxyethylene ether, tricresyl phosphate, antioxidant 2246, nano zinc oxide and accelerator DM is 40:18:10:15:5:8:1:2:1; 5. After the surface layer rubber mixture was allowed to stand for 15 hours, it was put into an open mixer and pressed into sheets at 150°C and 10 MPa to obtain a calendered surface layer 2; 6. Add chloropropylene rubber and styrene-butadiene rubber into the internal mixer and mix at 65°C for 10 minutes; 7. Add superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into the internal mixer and mix at 75°C for 15 minutes; 8. Add dioctyl sebacate, paraffin oil and accelerator CZ to the internal mixer in turn, and continue to mix at 75°C for 15 minutes to obtain the bottom rubber mixture; The mass ratio of chloropropylene rubber, styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ is 50:10:15:5:10:1:5:3:1; 9. After the bottom layer rubber mixture is allowed to stand for 8 hours, it is put into an open mixer and pressed into sheets at 150°C and 10 MPa to obtain a calendered bottom layer 1; 10. Cover the calendered surface layer 2 on the calendered bottom layer 1, then put it into the mold, send it into the drum vulcanizer, and vulcanize it at 160°C, 15MPa and 0.1m / min for 20min to finally make a double-layer composite non-flammable antistatic rubber mat.

[0033] Embodiment 2: like Figure 2 As shown, a method for preparing a double-layer composite non-flammable antistatic rubber pad comprises the following steps: 1. In a nitrogen-protected reactor, 2-chloro-1,3-butadiene and vinyl pyridine were copolymerized by emulsion copolymerization under the action of sodium stearate and ammonium persulfate, and the reaction was stirred at 50°C for 8 hours. The material was washed and dried to obtain modified chloroprene rubber; The mass ratio of 2-chloro-1,3-butadiene, vinylpyridine, sodium stearate and ammonium persulfate is 70:25:4.5:0.5; 2. Add the modified chloroprene rubber and nitrile rubber into an internal mixer and mix at 58°C for 9 minutes; 3. Add antioxidant 264 and nano zinc oxide into the internal mixer and continue mixing at 58°C for 6 minutes; 4. Add aluminum hydroxide, white carbon black, hexadecyltrimethylammonium bromide, tricresyl phosphate and accelerator DM into the internal mixer in sequence, and mix at 72°C for 11 minutes to prepare the surface layer rubber mixture; The mass ratio of modified chloroprene rubber, nitrile rubber, aluminum hydroxide, white carbon black, hexadecyltrimethylammonium bromide, tricresyl phosphate, antioxidant 264, nano zinc oxide and accelerator DM is 30:16:14:15:10:6:6:2:1; 5. After the surface layer rubber mixture was allowed to stand for 18 hours, it was put into an open mixer and pressed into sheets at 152°C and 11 MPa to obtain a calendered surface layer 2; 6. Add chloropropylene rubber and styrene-butadiene rubber into the internal mixer and mix at 68°C for 11 minutes; 7. Add superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into the internal mixer and mix at 78°C for 16 minutes; 8. Add dioctyl sebacate, paraffin oil and accelerator CZ to the internal mixer in sequence, and continue to mix at 78°C for 16 minutes to obtain the bottom rubber mixture; The mass ratio of chloropropylene rubber, styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ is 42:12:15:6:12:1:6:5:1; 9. After the bottom layer rubber mix was allowed to stand for 10 hours, it was put into an open mixer and pressed into sheets at 152°C and 11 MPa to obtain a calendered bottom layer 1; 10. Cover the calendered surface layer 2 on the calendered bottom layer 1, then put it into a mold, send it into a drum vulcanizer, and vulcanize it at 162°C, 16MPa and 0.2m / min for 22min to finally make a double-layer composite non-flammable antistatic rubber mat.

[0034] Embodiment 3: like Figure 2 As shown, a method for preparing a double-layer composite non-flammable antistatic rubber pad comprises the following steps: 1. In a nitrogen-protected reactor, 2-chloro-1,3-butadiene and vinyl pyridine were copolymerized by emulsion copolymerization under the action of sodium dodecyl sulfate and potassium persulfate, and the reaction was stirred at 42°C for 12 hours. The material was washed and dried to obtain modified chloroprene rubber; The mass ratio of 2-chloro-1,3-butadiene, vinylpyridine, sodium dodecyl sulfate and potassium persulfate is 78:18:3.2:0.8; 2. Add the modified chloroprene rubber and nitrile rubber into an internal mixer and mix them at 60°C for 10 minutes; 3. Add antioxidant 2246 and nano zinc oxide into the internal mixer and continue mixing at 60°C for 7 minutes; 4. Add aluminum hydroxide, white carbon black, octadecyl dimethyl benzyl ammonium chloride, tricresyl phosphate and accelerator DM to the internal mixer in sequence, and mix at 75°C for 12 minutes to prepare the surface layer rubber mixture; The mass ratio of modified chloroprene rubber, nitrile rubber, aluminum hydroxide, white carbon black, octadecyl dimethyl benzyl ammonium chloride, tricresyl phosphate, antioxidant 2246, nano zinc oxide and accelerator DM is 42:17:12:13:6:4:2:3:1; 5. After the surface layer rubber mixture was allowed to stand for 20 hours, it was put into an open mixer and pressed into sheets at 155°C and 12 MPa to obtain a calendered surface layer 2; 6. Add chloropropylene rubber and styrene-butadiene rubber into the internal mixer and mix at 70°C for 12 minutes; 7. Add superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into the internal mixer and mix at 80°C for 17 minutes; 8. Add dioctyl sebacate, paraffin oil and accelerator CZ to the internal mixer in sequence, and continue to mix at 80°C for 17 minutes to obtain the bottom rubber mixture; The mass ratio of chloropropylene rubber, styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ is 42:11:16:6:11:2:7:4:1; 9. After the bottom layer rubber mix is ​​left to stand for 12 hours, it is put into an open mixer and pressed into sheets at 155°C and 12 MPa to obtain a calendered bottom layer 1; 10. Cover the calendered surface layer 2 on the calendered bottom layer 1, then put it into a mold, send it into a drum vulcanizer, and vulcanize it at 165°C, 17MPa and 0.3m / min for 22min to finally make a double-layer composite non-flammable antistatic rubber mat.

[0035] Embodiment 4: like Figure 2 As shown, a method for preparing a double-layer composite non-flammable antistatic rubber pad comprises the following steps: 1. In a nitrogen-protected reactor, 2-chloro-1,3-butadiene and vinyl pyridine were copolymerized by emulsion copolymerization under the action of sodium dodecylbenzene sulfonate and ammonium persulfate, and the reaction was stirred at 48°C for 9 hours. The material was washed and dried to obtain modified chloroprene rubber; The mass ratio of 2-chloro-1,3-butadiene, vinylpyridine, sodium dodecylbenzenesulfonate and ammonium persulfate is 80:15:4.4:0.6; 2. Add the modified chloroprene rubber and nitrile rubber into the internal mixer and mix them at 62°C for 11 minutes; 3. Add antioxidant 264 and nano zinc oxide into the internal mixer and continue mixing at 62°C for 8 minutes; 4. Add aluminum hydroxide, white carbon black, fatty alcohol polyoxyethylene ether, tricresyl phosphate and accelerator DM into the internal mixer in sequence, and mix at 78°C for 13 minutes to prepare the surface layer rubber mixture; The mass ratio of modified chloroprene rubber, nitrile rubber, aluminum hydroxide, white carbon black, fatty alcohol polyoxyethylene ether, tricresyl phosphate, antioxidant 264, nano zinc oxide and accelerator DM is 38:20:13:12:7:5:1:2:2; 5. After the surface layer rubber mixture was allowed to stand for 24 hours, it was put into an open mixer and pressed into sheets at 158°C and 14 MPa to obtain a calendered surface layer 2; 6. Add chloropropylene rubber and styrene-butadiene rubber into the internal mixer and mix at 72°C for 13 minutes; 7. Add superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into the internal mixer and mix at 82°C for 18 minutes; 8. Add dioctyl sebacate, paraffin oil and accelerator CZ to the internal mixer in sequence, and continue to mix at 82°C for 18 minutes to obtain the bottom rubber mixture; The mass ratio of chloropropylene rubber, styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ is 47:10:15:8:10:1:5:3:1; 9. After the bottom layer rubber mixture was allowed to stand for 6 hours, it was put into an open mixer and pressed into sheets at 158°C and 14 MPa to obtain a calendered bottom layer 1; 10. Cover the calendered surface layer 2 on the calendered bottom layer 1, then put it into a mold, send it into a drum vulcanizer, and vulcanize it at 168°C, 17MPa and 0.15m / min for 23min to finally make a double-layer composite non-flammable antistatic rubber mat.

[0036] Embodiment 5:

[0037] like Figure 2 As shown, a method for preparing a double-layer composite non-flammable antistatic rubber pad comprises the following steps: 1. In a nitrogen-protected reactor, 2-chloro-1,3-butadiene and vinyl pyridine were copolymerized by emulsion copolymerization under the action of sodium stearate and potassium persulfate, and the reaction was stirred at 40°C for 11 hours. The material was washed and dried to obtain modified chloroprene rubber; The mass ratio of 2-chloro-1,3-butadiene, vinylpyridine, sodium stearate and potassium persulfate is 74:22:3.5:0.5; 2. Add modified chloroprene rubber and nitrile rubber into an internal mixer and mix at 65°C for 12 minutes; 3. Add antioxidant 2246 and nano zinc oxide into the internal mixer and continue mixing at 65°C for 10 minutes; 4. Add aluminum hydroxide, white carbon black, hexadecyltrimethylammonium bromide, tricresyl phosphate and accelerator DM to the internal mixer in sequence, and mix at 80°C for 15 minutes to prepare the surface layer rubber mixture; The mass ratio of modified chloroprene rubber, nitrile rubber, aluminum hydroxide, white carbon black, hexadecyltrimethylammonium bromide, tricresyl phosphate, antioxidant 2246, nano zinc oxide and accelerator DM is 50:16:10:12:5:3:1:2:1; 5. After the surface layer rubber mixture was allowed to stand for 12 hours, it was put into an open mixer and pressed into sheets at 160°C and 15 MPa to obtain a calendered surface layer 2; 6. Add chloropropylene rubber and styrene-butadiene rubber into the internal mixer and mix at 75°C for 15 minutes; 7. Add superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into the internal mixer and mix at 85°C for 20 minutes; 8. Add dioctyl sebacate, paraffin oil and accelerator CZ to the internal mixer in turn, and continue to mix at 85°C for 20 minutes to obtain the bottom rubber mixture; The mass ratio of chloropropylene rubber, styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ is 50:10:15:5:10:1:5:3:1; 9. After the bottom layer rubber mix is ​​left to stand for 10 hours, it is put into an open mixer and pressed into sheets at 160°C and 15 MPa to obtain a calendered bottom layer 1; 10. Cover the calendered surface layer 2 on the calendered bottom layer 1, then put it into the mold, send it into the drum vulcanizer, and vulcanize it at 170°C, 18MPa and 0.2m / min for 25min to finally make a double-layer composite non-flammable antistatic rubber mat.

[0038] Embodiment 6:

[0039] like Figure 2As shown, a method for preparing a double-layer composite non-flammable antistatic rubber pad comprises the following steps: 1. In a nitrogen-protected reactor, 2-chloro-1,3-butadiene and vinyl pyridine were copolymerized by emulsion copolymerization under the action of sodium dodecyl sulfate and ammonium persulfate, and the reaction was stirred at 50°C for 8.5 hours. The material was washed and dried to obtain modified chloroprene rubber; The mass ratio of 2-chloro-1,3-butadiene, vinylpyridine, sodium dodecyl sulfate and ammonium persulfate is 77:20:2.8:0.2; 2. Add the modified chloroprene rubber and nitrile rubber into an internal mixer and mix at 57°C for 9 minutes; 3. Add antioxidant 264 and nano zinc oxide into the internal mixer and continue mixing at 57°C for 7 minutes; 4. Add aluminum hydroxide, white carbon black, octadecyl dimethyl benzyl ammonium chloride, tricresyl phosphate and accelerator DM to the internal mixer in sequence, and mix at 73°C for 12 minutes to prepare the surface layer rubber mixture; The mass ratio of modified chloroprene rubber, nitrile rubber, aluminum hydroxide, white carbon black, octadecyl dimethyl benzyl ammonium chloride, tricresyl phosphate, antioxidant 264, nano zinc oxide and accelerator DM is 46:17:13:10:5:4:1:3:1; 5. After the surface layer rubber mixture was allowed to stand for 16 hours, it was put into an open mixer and pressed into sheets at 153°C and 12 MPa to obtain a calendered surface layer 2; 6. Add chloropropylene rubber and styrene-butadiene rubber into the internal mixer and mix at 67°C for 12 minutes; 7. Add superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into the internal mixer and mix at 77°C for 17 minutes; 8. Add dioctyl sebacate, paraffin oil and accelerator CZ to the internal mixer in turn, and continue to mix at 77°C for 17 minutes to obtain the bottom rubber mixture; The mass ratio of chloropropylene rubber, styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ is 43:12:16:6:11:1:6:3:2; 9. After the bottom layer rubber mixture was allowed to stand for 9 hours, it was put into an open mixer and pressed into sheets at 153°C and 12 MPa to obtain a calendered bottom layer 1; 10. Cover the calendered surface layer 2 on the calendered bottom layer 1, then put it into a mold, send it into a drum vulcanizer, and vulcanize it at 163°C, 17MPa and 0.25m / min for 24min to finally make a double-layer composite non-flammable antistatic rubber mat.

[0040] Comparative Example 1: A method for preparing a double-layer composite non-flammable antistatic rubber pad comprises the following steps: 1. Put the unmodified chloroprene rubber and nitrile rubber into the internal mixer and mix them at 55°C for 8 minutes; 2. Add antioxidant 2246 and nano zinc oxide into the internal mixer and continue mixing at 55°C for 5 minutes; 3. Add aluminum hydroxide, white carbon black, fatty alcohol polyoxyethylene ether, tricresyl phosphate and accelerator DM into the internal mixer in sequence, and mix at 70°C for 10 minutes to prepare the surface layer rubber mixture; The mass ratio of modified chloroprene rubber, nitrile rubber, aluminum hydroxide, white carbon black, fatty alcohol polyoxyethylene ether, tricresyl phosphate, antioxidant 2246, nano zinc oxide and accelerator DM is 40:18:10:15:5:8:1:2:1; 4. After the surface layer mixed rubber is allowed to stand for 15 hours, it is put into an open mixer and pressed into sheets at 150°C and 10 MPa to obtain a calendered surface layer 2; 5. Add chloropropylene rubber and styrene-butadiene rubber into the internal mixer and mix at 65°C for 10 minutes; 6. Add superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into the internal mixer and mix at 75°C for 15 minutes; 7. Add dioctyl sebacate, paraffin oil and accelerator CZ to the internal mixer in turn, and continue to mix at 75°C for 15 minutes to obtain the bottom rubber mixture; The mass ratio of chloropropylene rubber, styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ is 50:10:15:5:10:1:5:3:1; 8. After the bottom layer rubber mix is ​​left to stand for 8 hours, it is put into an open mixer and pressed into sheets at 150°C and 10 MPa to obtain a calendered bottom layer 1; 9. Cover the calendered surface layer 2 on the calendered bottom layer 1, then put it into the mold, send it into the drum vulcanizer, and vulcanize it at 160°C, 15MPa and 0.1m / min for 20min to finally make a double-layer composite non-flammable antistatic rubber mat.

[0041] Comparative Example 2: A method for preparing a double-layer composite non-flammable antistatic rubber pad comprises the following steps: 1. Put the styrene-modified chloroprene rubber and nitrile rubber into an internal mixer and mix them at 60°C for 10 minutes; 2. Add antioxidant 2246 and nano zinc oxide into the internal mixer and continue to mix at 60°C for 7 minutes; 3. Add aluminum hydroxide, white carbon black, octadecyl dimethyl benzyl ammonium chloride, tricresyl phosphate and accelerator DM to the internal mixer in sequence, and mix at 75°C for 12 minutes to prepare the surface layer rubber mixture; The mass ratio of modified chloroprene rubber, nitrile rubber, aluminum hydroxide, white carbon black, octadecyl dimethyl benzyl ammonium chloride, tricresyl phosphate, antioxidant 2246, nano zinc oxide and accelerator DM is 42:17:12:13:6:4:2:3:1; 4. After the surface layer rubber mixture was allowed to stand for 20 hours, it was put into an open mixer and pressed into sheets at 155°C and 12 MPa to obtain a calendered surface layer 2; 5. Add chloropropylene rubber and styrene-butadiene rubber into the internal mixer and mix at 70°C for 12 minutes; 6. Add superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into the internal mixer and mix at 80°C for 17 minutes; 7. Add dioctyl sebacate, paraffin oil and accelerator CZ to the internal mixer in turn, and continue to mix at 80°C for 17 minutes to obtain the bottom rubber mixture; The mass ratio of chloropropylene rubber, styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ is 42:11:16:6:11:2:7:4:1; 8. After the bottom layer rubber mix was allowed to stand for 12 hours, it was put into an open mixer and pressed into sheets at 155°C and 12 MPa to obtain a calendered bottom layer 1; 9. Cover the calendered surface layer 2 on the calendered bottom layer 1, then put it into the mold, send it into the drum vulcanizer, and vulcanize it at 165°C, 17MPa and 0.3m / min for 22min to finally make a double-layer composite non-flammable antistatic rubber mat.

[0042] Comparative Example 3: A method for preparing a double-layer composite non-flammable antistatic rubber pad comprises the following steps: 1. Put the vinyl pyridine modified butadiene rubber and nitrile rubber into an internal mixer and mix them at 57°C for 9 minutes; 2. Add antioxidant 264 and nano zinc oxide into the internal mixer and continue mixing at 57°C for 7 minutes; 3. Add aluminum hydroxide, white carbon black, octadecyl dimethyl benzyl ammonium chloride, tricresyl phosphate and accelerator DM to the internal mixer in sequence, and mix at 73°C for 12 minutes to prepare the surface layer rubber mixture; The mass ratio of modified chloroprene rubber, nitrile rubber, aluminum hydroxide, white carbon black, octadecyl dimethyl benzyl ammonium chloride, tricresyl phosphate, antioxidant 264, nano zinc oxide and accelerator DM is 46:17:13:10:5:4:1:3:1; 4. After the surface layer rubber mixture was allowed to stand for 16 hours, it was put into an open mixer and pressed into sheets at 153°C and 12 MPa to obtain a calendered surface layer 2; 5. Add chloropropylene rubber and styrene-butadiene rubber into the internal mixer and mix at 67°C for 12 minutes; 6. Add superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into the internal mixer and mix at 77°C for 17 minutes; 7. Add dioctyl sebacate, paraffin oil and accelerator CZ to the internal mixer in turn, and continue to mix at 77°C for 17 minutes to obtain the bottom rubber mixture; The mass ratio of chloropropylene rubber, styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ is 43:12:16:6:11:1:6:3:2; 8. After the bottom layer rubber mix was allowed to stand for 9 hours, it was put into an open mixer and pressed into sheets at 153°C and 12 MPa to obtain a calendered bottom layer 1; 9. Cover the calendered surface layer 2 on the calendered bottom layer 1, then put it into the mold, send it into the drum vulcanizer, and vulcanize it at 163°C, 17MPa and 0.25m / min for 24min to finally make a double-layer composite non-flammable antistatic rubber mat.

[0043] With reference to GB / T 11210-2014, the resistance test of the double-layer composite non-flammable antistatic rubber mat prepared in the examples and comparative examples of the present application was carried out to reflect its antistatic performance.

[0044] With reference to GB50209-2010, the non-flammability test method of non-flammable (explosion-proof) building floor materials and their products was used to test the non-flammability of the double-layer composite non-flammable antistatic rubber mats prepared in the examples and comparative examples of the present application.

[0045] Referring to GB / T 39697.2-2020, the surface roughness of the double-layer composite non-flammable antistatic rubber pad prepared in the examples and comparative examples of the present application was tested using a profilometer.

[0046] In addition, the double-layer composite non-flammable antistatic rubber pad prepared in the present application was also compared with other competing products in terms of performance tests, as shown in Tables 2 and 3.

[0047] Table 1 Performance test results of the double-layer composite non-flammable antistatic rubber pads prepared in the examples and comparative examples

[0048] It can be seen from Table 1 that the non-ignition performance of Examples 1 to 6 at a grinding wheel speed of 600 r / min and a pressure of 10 N is better than that of Comparative Examples 1 to 3, and the resistance of Examples 1 to 6 is higher than that of Comparative Examples 1 to 3, which indirectly reflects that the antistatic performance of Examples 1 to 6 is better than that of Comparative Examples 1 to 3.

[0049] This is because, in Examples 1 to 6, the surface matrix material of the double-layer composite non-flammable antistatic rubber pad is modified chloroprene rubber, which is copolymerized by 2-chloro-1,3-butadiene and vinyl pyridine. On the one hand, the strong polarity of the vinyl pyridine unit changes the surface properties of the rubber molecules, so that the modified chloroprene rubber has better surface activity, reduces the interfacial tension between the filler and the rubber, so that the filler is dispersed in the surface modified chloroprene rubber matrix, enhances the mechanical properties and stability of the modified chloroprene rubber, and makes it more wear-resistant. On the other hand, the surface layer of the rubber pad is very smooth (the surface roughness Ra value is 0.8~1.6μm), and even if the surface is attached with charges, it is easy to disperse evenly, and it is not easy to cause static electricity accumulation due to surface roughness, so it is difficult to generate static electricity sparks. Finally, the rigid pyridine ring structure with strong polarity will form a dipole interaction with the chlorine atoms in the molecular chain, increase the cohesion between the polymer chains, and improve the flame retardant properties of the modified chloroprene rubber. The combination of multiple aspects makes the surface layer have good non-inflammability. Further, under the joint action of other fillers and additives in the surface layer, the rubber pad obtained still has stable antistatic properties under frequent friction conditions and other harsh environments. In addition, the bottom matrix material of the double-layer composite non-inflammable antistatic rubber pad is chloropropylene rubber, which has excellent chemical stability. After being combined with fillers and additives such as superconducting carbon black and metal powder, it can quickly conduct the generated static electricity to the ground to avoid static electricity accumulation and sparks. After the two layers are compounded by vulcanization and pressure, the combination is firm, which further enhances the antistatic and non-inflammable properties of the obtained double-layer composite non-inflammable antistatic rubber pad.

[0050] In Comparative Example 1, the surface layer matrix material of the rubber pad is chloroprene rubber, which has not been modified with vinyl pyridine, so the filler is poorly dispersed in the surface layer rubber matrix, and due to the absence of a rigid pyridine ring structure with strong polarity, it will not form a dipole interaction with the chlorine atoms in the molecular chain, which ultimately leads to the poor non-fire performance of the rubber pad. In Comparative Example 2, the surface layer matrix material of the rubber pad is chloroprene rubber, which has been modified, but styrene is used instead of vinyl pyridine, and it will not form a dipole interaction with the chlorine atoms in the molecular chain, and the non-fire performance is poor. In Comparative Example 3, the surface layer matrix material of the rubber pad is cis-butyl rubber instead of chloroprene rubber. Although it has been modified and vinyl pyridine is used, it will not form a dipole interaction with the molecular chain, and the non-fire performance is also poor.

[0051] Table 2 Comparison of physical properties of Example 1 and competing products

[0052] As can be seen from Table 2, the tensile strength, elongation at break, change rate of elongation at break under various conditions (hot air aging, oil environment, isopropanol immersion) and volume change rate of Example 1 are significantly better than those of competing products. This is also because the strong polarity of the vinyl pyridine unit changes the surface properties of the rubber molecules, making the modified chloroprene rubber have better surface activity, reducing the interfacial tension between the filler and the rubber, so that the filler is dispersed in the surface modified chloroprene rubber matrix, enhancing the mechanical properties and stability of the modified chloroprene rubber.

[0053] Table 3 Comparison of the endurance performance of Example 1 and competing products under different environments

[0054] As shown in Table 3, compared with its competitors, Example 1 can still maintain qualified antistatic performance in harsh environments (hot air in ovens). This is because the rigid pyridine ring structure with strong polarity forms a dipole interaction with the chlorine atoms in the molecular chain, which increases the cohesion between polymer chains and improves the flame retardant properties of the modified chloroprene rubber; further, under the combined effect of other fillers and additives in the surface layer, the rubber pad obtained still has stable antistatic properties under frequent friction conditions and other harsh environments.

[0055] The above results show and describe the basic principles and main features of the present application as well as the advantages of the present application.

[0056] Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present application. Without departing from the spirit and scope of the present application, the present application may have various changes and improvements, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection sought in the present application is defined by the equivalents of the attached claims.

Claims

1. A double-layer composite non-flammable antistatic rubber pad, comprising a bottom layer (1) and a surface layer (2) attached to one side of the bottom layer (1); characterized in that: The surface layer (2) comprises modified chloroprene rubber; the bottom layer (1) comprises chloropropylene rubber; the modified chloroprene rubber is copolymerized from 2-chloro-1,3-butadiene and vinyl pyridine; the structure of the modified chloroprene rubber is: , Wherein, n is an integer in the range of 10 to 20; m is an integer in the range of 50 to 100; and the surface roughness Ra value of the surface layer (2) is 0.8 to 1.6 μm.

2. A double-layer composite non-inflammable antistatic rubber pad according to claim 1, characterized in that: The surface layer (2) also includes nitrile rubber, aluminum hydroxide, white carbon black, an antistatic agent, tricresyl phosphate, an antioxidant, nano zinc oxide and a promoter DM.

3. A double-layer composite non-inflammable antistatic rubber pad according to claim 2, characterized in that: The antistatic agent includes at least one of fatty alcohol polyoxyethylene ether, hexadecyltrimethylammonium bromide and octadecyldimethylbenzylammonium chloride.

4. A double-layer composite non-inflammable antistatic rubber pad according to claim 2, characterized in that: The antioxidant includes at least one of the antioxidant 2246 and the antioxidant 264 .

5. A double-layer composite non-inflammable antistatic rubber pad according to claim 2, characterized in that: In the surface layer (2), the mass ratio of modified chloroprene rubber, nitrile rubber, aluminum hydroxide, white carbon black, antistatic agent, tricresyl phosphate, antioxidant, nano zinc oxide and accelerator DM is (30-50): (15-20): (10-15): (10-20): (5-10): (3-10): (1-3): (2-5): (1-2).

6. A double-layer composite non-inflammable antistatic rubber pad according to claim 1, characterized in that: The bottom layer (1) also includes styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ.

7. A double-layer composite non-inflammable antistatic rubber pad according to claim 6, characterized in that: In the bottom layer (1), the mass ratios of chloropropylene rubber, styrene-butadiene rubber, superconducting carbon black, aluminum powder, calcium carbonate, γ-glycidyloxypropyltrimethoxysilane, dioctyl sebacate, paraffin oil and accelerator CZ are (40-50): (10-15): (15-25): (5-10): (10-20): (1-3): (5-10): (3-10): (1-2).

8. The method for preparing a double-layer composite non-inflammable antistatic rubber pad according to any one of claims 1 to 7, characterized in that: The following steps are involved: In a nitrogen-protected reactor, 2-chloro-1,3-butadiene and vinyl pyridine are copolymerized by an emulsion copolymerization method under the action of an emulsifier and an initiator, the reaction is stirred at a first set temperature for a first set time, and the material is washed and dried to obtain a modified chloroprene rubber; Putting the modified chloroprene rubber and the nitrile rubber into an internal mixer, and mixing them at a second set temperature for a second set time; Adding antioxidant and nano zinc oxide into an internal mixer, and continuing to internally mix at a second set temperature for a third set time; Adding aluminum hydroxide, white carbon black, antistatic agent, tricresyl phosphate and accelerator DM into the internal mixer in sequence, and mixing at the third set temperature for the fourth set time to prepare a surface layer rubber mixture; After the surface layer mixed rubber is allowed to stand for a fifth set time, it is put into an open mixer and pressed into a sheet at a fourth set temperature and a first set pressure to obtain a calendered surface layer (2); Adding chloropropylene rubber and styrene-butadiene rubber into an internal mixer, and mixing at a fifth set temperature for a fourth set time; Adding superconducting carbon black, aluminum powder, calcium carbonate and γ-glycidyloxypropyltrimethoxysilane into an internal mixer, and mixing at a sixth set temperature for a sixth set time; Add dioctyl sebacate, paraffin oil and accelerator CZ to the internal mixer in sequence, and continue to mix at the sixth set temperature for the sixth set time to obtain a base rubber mixture; After the bottom layer rubber mixture is allowed to stand for a seventh set time, it is put into an open mixer and pressed into a sheet at a fourth set temperature and a first set pressure to obtain a calendered bottom layer (1); The calendered surface layer (2) is covered on the calendered bottom layer (1), then placed in a mold, and sent to a drum vulcanizer, and vulcanized for an eighth set time at a seventh set temperature, a second set pressure and a first vulcanization speed, to finally produce a double-layer composite non-flammable antistatic rubber mat.

9. The method for preparing a double-layer composite non-inflammable antistatic rubber pad according to claim 8, characterized in that: The emulsifier includes any one of sodium dodecylbenzene sulfonate, sodium stearate and sodium dodecyl sulfate; the initiator includes any one of potassium persulfate and ammonium persulfate; the mass ratio of 2-chloro-1,3-butadiene, vinyl pyridine, emulsifier and initiator is (70~85): (10~30): (2~5): (0.2~0.8).

10. The method for preparing a double-layer composite non-inflammable antistatic rubber pad according to claim 8, characterized in that: The first set temperature is 40~50℃; the second set temperature is 55~65℃; the third set temperature is 70~80℃; the fourth set temperature is 150~160℃; the fifth set temperature is 65~75℃; the sixth set temperature is 75~85℃; the seventh set temperature is 160~170℃; the first setting time is 8~12h; the second setting time is 8~12min; the third setting time is 5~10min; the fourth setting time is 10~15min; the fifth setting time is 12~24h; the sixth setting time is 15~20min; the seventh setting time is 6~12h; the eighth setting time is 20~25min; the first setting pressure is 10~15MPa; the second setting pressure is 15~18MPa; the first vulcanization speed is 0.1~0.3m / min.

Citation Information

Patent Citations

  • Antistatic floor mat

    CN106079755A

  • Spark-oil-resistant rubber protective cover and preparation method thereof

    CN103881169A

  • Rubber composition, laminate, and conveyor belt

    CN107709434A

  • Vibration-absorption, wear-resisting and antibacterial rubber floor mat and preparation method thereof

    CN109054190A

  • Long-acting environment-friendly flame-retardant anti-static rubber pad and preparation method thereof

    CN119567662A